The Influence of Inquiry Laboratory and Phyphox-Excel on Physics Concept Understanding in View of Students' Self-Regulated Learning - Muhammad Sayyadi (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2026)
The achievement of learning outcomes is not only influenced by models, methods, or learning strategies, but there are several other factors that can affect the achievement of the learning process. The selection of the right model, method, or media will facilitate educators in creating a pleasant learning atmosphere and in achieving learning outcomes. The inquiry laboratory learning model, assisted by Phyphox-Excel, can help students understand physics concepts, both during the learning process (performance) and at the end of learning (cognitive aspect). The purpose of this research is to determine the extent of the influence of the inquiry laboratory model assisted by Phyphox-Excel on students' understanding of physics concepts, as reflected in their Self-Regulated Learning (SRL). Data on students' understanding of concepts were collected through performance assessments and cognitive tests administered at the end of the learning. The results obtained from this research are: (1) the performance assessment of students learning with inquiry laboratory and Phyphox-Excel application is higher than those learning with inquiry laboratory without Phyphox-Excel, (2) the performance assessment of students with high SRL is higher than that of students with low SRL, (3) there is no interaction between the inquiry laboratory Model and SRL on student performance outcomes, (4) there are differences between inquiry laboratory with Phyphox-Excel application and inquiry laboratory without Phyphox-Excel on students' cognitive abilities, (5) there are differences in cognitive abilities between students with high SRL and students with low SRL, (6) there is an interaction between inquiry laboratory and SRL on students' cognitive abilities.